TEACHING READING COMPREHENSION BY USING SUMMARIZING STRATEGY TO THE ELEVENTH GRADE STUDENTS OF THE STATE SENIOR HIGH SCHOOL 1 OF PALEMBANG - YUSPAR UZER (Universitas PGRI Palembang, 2016)
Abstract The formulation of the of this study was “Is it effective teaching reading comprehension by using summarizing strategy to the eleventh grade students of the State Senior High School 1 of Palembang?” Therefore, the purpose of this study was to find out the effectiveness of teaching reading comprehension by using summarizing strategy to the eleventh grade students of the State Senior High School 1 of Palembang. The population of this study was all the eleventh grade students of the State Senior High School 1 of Palembang in academic year 2013/2014. The sample was taken class XI.1. that consists of 35 students. The methods of this study were experimental method by using the convenience non random sampling. In collecting the data, the written test was given consisted of 24 questions where 4 items were essay questions, 10 items multiple choice, 10 items short answer. The pretest was given in order to know the students’ achievement and the post-test was given after giving the treatment. To analyze the data, the matched t-test formula was applied. Based on the finding of the study, the writer found that the average score in the pre-test was 6.44 and the average score that the students got in post test 7, 52. The result of t-test calculation indicates that by using summarizing strategy was effective to implement in teaching reading comprehension by using summarizing strategy to the eleventh grade students of the State Senior High School 1 of Palembang because the t-obtained (12.00) was higher that t-table. Therefore, the alternative hypothesis (Ha) was accepted. It can be concluded that it was effective in teaching reading comprehension by using summarizing strategy to the eleventh grade students of the State Senior High School 1 of Palembang. Keywords: teaching, reading comprehension,summarizing strategy